Critical analysis of present research and education on soil and water conservation - SENTÃS, ILDEFONSO PLA (Journal of Soil and Water Conservation, 2020)
Soil degradation is due to complex processes depending on soil properties, relief, climate and soil and crop management practices. It is frequently induced by social-economic factors and wrong development policies. Control of soil degradation and its effects will depend on an adequate planning of the use and management of soil and water resources. That requires a previous identification and evaluation of the soil degradation processes and of the cause-effects relations of the different generated problems. The problems of soil and water degradation, as opposite to conservation of both resources, are growing in the whole World, and this is partially due to a deficient evaluation of the processes and causes of such degradation for every particular situation, and to the frequent use of empirical approaches for the selection of soil and water conservation practices. Those deficiencies are mainly related to non adequate education and training in soil science and related aspects (agronomy, hydrology, etc) of the people responsible for planning environmental conservation, including soil and water resources, leading to the use of very empirical and standardized approaches. At the same time, people presently doing research on soil and water conservation, generally use very theoretical approaches, mainly based on laboratory measurements, or very empirical deductions based on pedo-transfer functions. In most of the cases there is a lack of a clear connection and application of these approaches for field evaluations of soil and water interactions, leading to practical and efficient conservation practices adapted to variable combinations of biophysical and social-economic conditions. This is reflected in most of the papers about soil and water conservation being published nowadays in the different journals. The growing scarcity of available funds, at local and international level, for more integral studies on soil and water conservation at field level, may have contributed to both problems. Besides, potential problems of global climate changes due to greenhouse gases, have concentrated the last 10-20 years the attention of many organizations and institutions, decreasing the resources dedicated to the evaluation of present soil degradation processes and practices of soil and water conservation to control them, unless they are related to the still non very well defined potential global climate changes. Nowadays, the processes of soil and water degradation and their consequences, including catastrophic events, still may be attributed more to non adequate land use and management than to the mostly hypothetical future global climate changes. To solve the previously explained situation, there are required changes, with provision of the appropriate funds: in the orientation and level of education of the soil and water conservation specialists, pursuing a more holistic approach, integrating theory and field work; in the research institutions, promoting more integral studies with the cooperation among soil scientists and scientists of other related disciplines; and in the journals policy, facilitating and stimulating the publication of papers based on more integral studies and research, with results validated at field level, instead of the ones only based on empirical or very isolated non applicable studies